Metal distribution and Sr and Pb stable isotope ratios for sediment samples of ATAIR cruise AT261 - Anna Ebeling; Nathalie Voigt; Carlotta Pehlke; Bettina Rust; Andrea Pieper; Tristan Zimmermann; Daniel Pröfrock (PANGAEA, 2023)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment samples were taken in the surrounding and within different wind farms of the German Bight in April 2018 within the context of the Hereon-BSH project OffChEm. The surface sediment samples were taken by a box grab, homogenized, freeze-dried and wet-sieved to gain the <20 μm grain size fraction. The <20 μm grain size fraction was acid digested and measured by ICP-MS/MS for their (trace) metal mass fractions. The Sr and Pb isotope ratios were measured by MC ICP-MS after an automated matrix separation with a prepFAST MC system.